Proteomics Approach Identifies Factors Associated With the Response to Low‐Density Lipoprotein Apheresis Therapy in Patients With Steroid‐Resistant Nephrotic Syndrome. Issue 2 (14th January 2016) - Kuribayashi‐Okuma, Emiko; Shibata, Shigeru; Arai, Shigeyuki; Ota, Tatsuru; Watanabe, Sumiyo; Hisaki, Harumi; Okazaki, Tomoki; Toda, Tosifusa; Uchida, Shunya
Abstract: Low‐density lipoprotein apheresis (LDL‐A) has been shown to reduce proteinuria in a subgroup of nephrotic syndrome patients refractory to immunosuppressive therapy. Factors influencing the efficacy of LDL‐A in nephrotic syndrome are completely unknown. Using a proteomics approach, we aimed to identify biological markers that predict the response to LDL‐A in patients with steroid‐resistant nephrotic syndrome (SRNS). Identification of plasma proteins bound to the dextran‐sulfate column at the first session of LDL‐A was determined by mass spectrometry. To investigate biological factors associated with the response to LDL‐A, we compared profiles of column‐bound proteins between responders (defined by more than 50% reduction of proteinuria after the treatment) and non‐responders by 2‐dimensional gel electrophoresis (2‐DE) coupled to mass spectrometry in seven patients with SRNS. Evaluation of proteins adsorbed to LDL‐A column in patients with SRNS revealed the identity of 62 proteins, which included apolipoproteins, complement components, and serum amyloid P‐component (SAP). Comparative analysis of the column‐bound proteins between responders and non‐responders by 2‐DE demonstrated that apolipoprotein E (APOE) and SAP levels were increased in non‐responders as compared with responders. These results were confirmed by western blotting. Moreover, serum levels of APOE and SAP were significantly higher in the non‐responder group than in the responder group by ELISA. Our data provide comprehensive analysis of proteins adsorbed by LDL‐A in SRNS, and demonstrate that the serum levels of APOE and SAP may be used to predict the response to LDL‐A in these patients.